2005
DOI: 10.4141/s04-055
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction and water content as factors affecting the growth of lodgepole pine seedlings on sandy clay loam soil

Abstract: . 2005. Soil compaction and water content as factors affecting the growth of lodgepole pine seedlings on sandy clay loam soil. Can. J. Soil Sci. 85: 667-679. The response of lodgepole pine (Pinus contorta Dougl. var. latifolia Engelman.) seedlings to three levels of soil compaction and water content was evaluated in raised beds filled with a sandy clay loam soil. In compacted soils, seedling survival, height, root collar diameter and root growth were reduced. Soil water regime was adjusted with irrigation to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 22 publications
1
23
0
2
Order By: Relevance
“…As mentioned before, we considered RBD exceeding 80% MBD (RBD > 0.80) as a soil density at which tree growth is probably reduced because of lowered air-fi lled porosity, reduced infi ltration, and higher mechanical resistance as proven by da Silva et al (1994) and Bulmer and Simpson (2005). Since Proctor density increases with increased water content up to MBD and decreases with a further increase of water content beyond MBD, the moisture-density relationship displays the shape of an inverse parabola resulting in a range of water content between both lower and upper water content limits associated with the 80% MBD thresholds on the dry and wet side of the parabola.…”
Section: Relative Bulk Densitymentioning
confidence: 99%
“…As mentioned before, we considered RBD exceeding 80% MBD (RBD > 0.80) as a soil density at which tree growth is probably reduced because of lowered air-fi lled porosity, reduced infi ltration, and higher mechanical resistance as proven by da Silva et al (1994) and Bulmer and Simpson (2005). Since Proctor density increases with increased water content up to MBD and decreases with a further increase of water content beyond MBD, the moisture-density relationship displays the shape of an inverse parabola resulting in a range of water content between both lower and upper water content limits associated with the 80% MBD thresholds on the dry and wet side of the parabola.…”
Section: Relative Bulk Densitymentioning
confidence: 99%
“…In a review of soil compaction studies, Graecen and Sands (1980) concluded that both thinning and clear-cut harvesting are forest management practices most likely to cause soil compaction, although quantitative data on the impact of thinning on soil compaction were not given. Compaction decreases soil porosity and reduces the movement of air, water and nutrients through the soil, which can reduce tree rooting space and tree growth, and negatively impact microbial populations, nutrient availability and organic matter decomposition (Brussaard and van Faassen 1994;Thibodeau et al 2000;Bulmer and Simpson 2005;von Wilpert and Scha¨ffer 2006).…”
Section: Mots Clé Smentioning
confidence: 99%
“…Cheatle (1991) found that tree survival and basal areas of Terminalia brasii were much lower on compacted soils. Detrimental effects on growth of Pinus contorta on a sandy clay loam soil were observed by Bulmer & Simpson (2005). Rhoades, Brosi, Dattilo & Vincelli (2003) showed that the mortality of Castanea dentata seedlings due to the incidence of Phytophthora root rot was largest in wet, compacted soils.…”
Section: Introductionmentioning
confidence: 99%